Understanding the Impacts of Lockdown during COVID-19 Pandemic on Financial Threat and Psychological Response among Sarawak Adults - Nurkhalida Suut; Aainaa Nasha Mohamad Azlan; Siti Jamilah Jamaluddin Jugah; Ting Chuong Hock; Nurul Husna Syaffa Amin; Muhmmad Ainul Rashyid Aris Mohd Aris Fadillah; Zurraini Arabi (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 03-2021) [August 2021]